2014
DOI: 10.1103/physrevc.90.014302
|View full text |Cite
|
Sign up to set email alerts
|

Merging of the islands of inversion atN=20andN=28

Abstract: The N=20 and N=28 "islands of inversion" are described by large scale shell model calculations with an extension of the interaction sdpf-u that makes it possible to mix configurations with different N ω or equivalently with different number of particles promoted from the sd-shell to the pf -shell. It allows to connect the classical sd-shell calculations below N=18 with the sd(protons)-pf(neutrons) calculations beyond N=24-26, for all the isotopes from Oxygen to Argon, using the same interaction. For some isoto… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
219
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 171 publications
(242 citation statements)
references
References 91 publications
20
219
1
2
Order By: Relevance
“…As a starting point we take the unperturbed values, based on the large-scale shell model calculations of Ref. [7], to be e 0 = 1.4 MeV, e 2 = 0.2 MeV and e 4 = 0 MeV.…”
Section: The Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…As a starting point we take the unperturbed values, based on the large-scale shell model calculations of Ref. [7], to be e 0 = 1.4 MeV, e 2 = 0.2 MeV and e 4 = 0 MeV.…”
Section: The Approachmentioning
confidence: 99%
“…Large scale shell-model calculations [7] however, predict the coexistence of 0p0h, 2p2h and 4p4h states in the low-lying excitation spectra of the N ∼ 20 Mg nuclei, calling into question the validity of a two-level approach. Inspired by these results, we have revisited the analysis of Fortune [5,8], extending it now to a three-level mixing.…”
Section: Introductionmentioning
confidence: 99%
“…In 1979 Simons et al [13] first identified the neutron-rich nucleus 35 Al produced in fragmentation of 40 Ar. Four decades later, except for some theoretical calculations [14][15][16][17][18], limited experimental information regarding the ground-state configuration of 35 Al is available. The ground-state information of a nucleus gives direct insight into the wave function.…”
Section: Introductionmentioning
confidence: 99%
“…Recently intruder configurations are found in the neutron rich nuclei around this shell gap [3,4,5,6,7]. Thus the nuclear structure study of these nuclei in this region is very important [8,9,10].…”
Section: Introductionmentioning
confidence: 99%